Labour's First Year : 1945-46 (London : Common Wealth Publications Committee, 1946)
1946 1946 1940s 27 pages WE ASK... Does it Pay? [Double Strikethrough] Is it Expedient? [Double Strikethrough] IS IT RIGHT? Published by Common Publications Committee, 44, Bloomsbury Street, W.C., and Printed by Fox Printing Press (T.U.), 637 Forest Road, London, E.17 15X/2/98/21